2011
DOI: 10.1177/030089161109700209
|View full text |Cite
|
Sign up to set email alerts
|

AKT Signaling Pathway in Invasive Ductal Carcinoma of the Breast: Correlation with ERα, ERβ and HER-2 Expression

Abstract: The current study suggested that activity of the Akt signaling pathway may indicate a poor prognosis in patients with breast carcinoma. The results implied that estrogen can activate the PI3K-Akt pathway through ERa and ERβ-independent mechanisms in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
(19 reference statements)
0
9
0
1
Order By: Relevance
“…cervical cancer), [36, 37] but the increased stability of p53 mut is increasingly observed to be prognostic in breast cancer [72]. EGFR/HER2 +ve and ERα +ve breast cancers have previously been described to have elevated AKT activity [73, 74], we therefore aimed to correlate phospho-S48-NPM staining, with EGFR/HER2 positivity, p53 staining and tumor stage. Interestingly, the highest levels of p53 mut segregated with advanced tumor stage and the degree of phospho-S48-NPM staining correlated with EGFR/HER2 positivity and increased p53 staining intensity indicative of p53 mut (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…cervical cancer), [36, 37] but the increased stability of p53 mut is increasingly observed to be prognostic in breast cancer [72]. EGFR/HER2 +ve and ERα +ve breast cancers have previously been described to have elevated AKT activity [73, 74], we therefore aimed to correlate phospho-S48-NPM staining, with EGFR/HER2 positivity, p53 staining and tumor stage. Interestingly, the highest levels of p53 mut segregated with advanced tumor stage and the degree of phospho-S48-NPM staining correlated with EGFR/HER2 positivity and increased p53 staining intensity indicative of p53 mut (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that endoplasmic reticulum stress-induced apoptosis is associated with a reduction in phospho-Akt (27,28). In addition, estrogen activates the PI3K-Akt pathway through ER α- and ER β-independent mechanisms in breast cancer (29,30). In the present study, the dephosphorylation of Akt at Ser473 was found to be involved in apoptosis induced by endoplasmic reticulum stress.…”
Section: Discussionmentioning
confidence: 99%
“…The serine/threonine kinase Akt plays an essential role in various cellular processes, including cell growth and proliferation, metabolism and cell survival. Immunohistochemical analyses have shown that Akt is activated in many types of carcinoma and preneoplastic lesions, and Akt activation is associated with tumor progression and poor prognosis in various human malignancies [23][24][25][26][27] . However, in NSCLCs, the results so far are conflicting.…”
Section: Discussionmentioning
confidence: 99%